Revisiting the relationship between maternal parenting behaviors and executive functions in young children: Effect of measurement methods - Wei, Wei; Lu, Wen-Ting; Huang, Min-Min; Li, Yan (Frontiers in Psychology, 2023)
The past decade of studies showed that parenting behaviors (e.g., warmth, autonomy, control) were associated with children’s executive functions (EF) in the early years (e.g., Bernier et al., 2010; Blair et al., 2014; Hertz et al., 2019; Merz et al., 2016; Regueiro et al., 2020). However, different measurement methods had been used across studies, making it hard to compare the effects of parenting and EF across studies. Therefore, the present study aimed to examine the effect of the measurement methods on the relationship between maternal behaviors and children’s EF among a group of Chinese preschoolers. One hundred and twenty-six children (62 boys; Mage = 48.35 months) were assessed with direct measures on children’s EF (inhibition and working memory tasks), and parenting behaviors of their mothers during interaction with children were observed and coded. Mothers reported their parenting practices and children’s difficulties in executive function. The results of structural equation modeling showed that the latent performance-based EF was uniquely predicted by maternal positive control and negative control in mother-child interaction, while children’s EF difficulties reported by mothers were predicted by all four aspects of mother-reported parenting, i.e., warmth and support, autonomy granting negatively, physical coercion and verbal hostility. Overall, the results suggested that the relationship between maternal parenting and children’s EF depends on the measurement methods of parenting and executive functions.